2014
DOI: 10.1007/s10562-014-1358-6
|View full text |Cite
|
Sign up to set email alerts
|

Study of Gas Phase m-Cresol Alkylation with Methanol on Solid Acid Catalysts

Abstract: The gas-phase alkylation of m-cresol with methanol was studied at 523 K on Al-MCM-41 and zeolites ZnY, HBEA, HZSM5 and HMCM22. The acidity was determined by ammonia TPD and FTIR of adsorbed pyridine. On acid sites of moderate strength (Al-MCM-41), initially the O-alkylation rate was higher than the C-alkylation rate. In contrast, formation of dimethylphenols by C-alkylation was highly favored on ZnY and HMCM22 which have both strong acidity although different nature; Lewis (ZnY) and Brønsted and Lewis (HMCM22)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 31 publications
1
12
0
Order By: Relevance
“…This further confirmed that the isomerization of m- cresol becomes a major reaction beyond 270 °C which lowered its availability in the feed and hence, conversion decreased . Moreover, the decrease in conversion after this temperature can be attributed to the formation of coke due to side/parallel reactions and pore blocking on the catalyst …”
Section: Results and Discussionsupporting
confidence: 52%
See 2 more Smart Citations
“…This further confirmed that the isomerization of m- cresol becomes a major reaction beyond 270 °C which lowered its availability in the feed and hence, conversion decreased . Moreover, the decrease in conversion after this temperature can be attributed to the formation of coke due to side/parallel reactions and pore blocking on the catalyst …”
Section: Results and Discussionsupporting
confidence: 52%
“…37 Moreover, the decrease in conversion after this temperature can be attributed to the formation of coke due to side/parallel reactions and pore blocking on the catalyst. 46 The selectivity to the alkylated products on iso-propylation of m-cresol as a function of temperature is included in Figure 8 (Tables S12−S15 in Supporting Information). The Oalkylation results in the formation of ether product, IPMCE, whereas, the C-alkylation leads to the formation of isopropylated m-cresols, (2-isopropyl-5-methylphenol (thymol), 4-isopropyl-3-methyphenol (4I-3MP), and 3-isopropyl-5-methylphenol (3I-5MP)) and di-iso-propylated products, (2,4-di-isopropyl-5-methylphenol (2,4DI-5MP) and 2,6-di-iso-propyl-3methylphenol (2,6DI-3MP)).…”
Section: Journal Of Chemical and Engineering Datamentioning
confidence: 99%
See 1 more Smart Citation
“…We relate this to different rates of the alkylation reactions of the aromatic products, which also contribute to suppressing repolymerization reactions. , It is reasonable to postulate that the lower alkylation activity is associated with the absence of Al. It is well-known that alkylation reactions (e.g., phenol alkylation with alcohols) are catalyzed by inorganic Lewis and/or Brønsted acids such as H 2 SO 4 , AlCl 3 , and BF 3 , as well as solid acids such as zeolites …”
Section: Resultsmentioning
confidence: 98%
“…It is well known that alkylation reactions (e.g., phenol alkylation with alcohols) are catalyzed by inorganic Lewis and/or Brønsted acids such as H2SO4, AlCl3, BF3, 57 as well as solid acids such as zeolites. 58 In order to establish whether differences in the alkylation activity can explain the better performance of the hydrotalcites derived catalysts, we carried out model reactions using phenol as reactant in supercritical ethanol (340 °C, 4 h, 1 g phenol, 40 ml ethanol). The reaction mixtures were analyzed by GC-MS and quantified by GC-FID.…”
Section: Varying the M 2+ /M 3+ Ratiomentioning
confidence: 99%